The orthotic treatment of juvenile hallux valgus - Kilmartin, Timothy Edward (1994)
Pronation of the foot is proposed as a possible aetiological factor in hallux valgus. Root type foot orthoses have been shown to restrict foot pronation and therefore have been used to treat hallux valgus.